2009
DOI: 10.1002/jcp.21885
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of transport and phosphorylation of glucose in cancer cells

Abstract: Metabolic control analysis of tumor glycolysis has indicated that hexokinase (HK) and glucose transporter (GLUT) exert the main flux control (71%). To understand why they are the main controlling steps, the GLUT and HK kinetics and the contents of GLUT1, GLUT2, GLUT3, GLUT4, HKI, and HKII were analyzed in rat hepatocarcinoma AS-30D and HeLa human cervix cancer. An improved protocol to determine the kinetic parameters of GLUT was developed with D-[2-(3)H-glucose] as physiological substrate. Kinetic analysis rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 67 publications
6
72
0
Order By: Relevance
“…Furthermore, increased glucose consumption serves to supply carbon to various anabolic pathways necessary for biomass duplication preceding mitosis 33 and induces resistance to classic chemotherapeutic agents. 10,34,35 Compelled by evidence that glucose transport may represent the principal ratedetermining step of glycolysis in tumor cells, 13,14 we have interrogated the glucose transporter family as a source of novel therapeutic targets. Our data clearly demonstrate myeloma dependence on GLUT4 activity, a phenomenon associated with the basal cell surface localization of the transporter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, increased glucose consumption serves to supply carbon to various anabolic pathways necessary for biomass duplication preceding mitosis 33 and induces resistance to classic chemotherapeutic agents. 10,34,35 Compelled by evidence that glucose transport may represent the principal ratedetermining step of glycolysis in tumor cells, 13,14 we have interrogated the glucose transporter family as a source of novel therapeutic targets. Our data clearly demonstrate myeloma dependence on GLUT4 activity, a phenomenon associated with the basal cell surface localization of the transporter.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Therefore, we established an unbiased real-time RT-PCR-based screen to determine relative expression levels of GLUTs 1 to 12 in 9 MM cell lines and NBLs ( Figure 1E). To avoid bias, myeloma lines were selected to broadly cover different genotypic disease subtypes.…”
Section: Cell Lines Overexpress Glut4 Glut8 and Glut11mentioning
confidence: 99%
See 1 more Smart Citation
“…Both live imaging and biochemical approaches demonstrated that GLUT4 expressed in HeLa cells was able to respond to insulin in an N-glycan-dependent manner, suggesting that HeLa cells, despite their lack of GLUT4 expression (40), retain the basic machinery required for insulin-mediated cellular signaling. Similar findings have previously been reported for noninsulin-responsive fibroblasts (21), although the detailed molecular mechanism of translocation may not be exactly the same as that in insulin-responsive adipocytes (41).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of glucose uptake by resveratrol in our study was linked to diminished glycolytic metabolism as evidenced by decreased lactate production. Among the major determinants of tumor glycolytic flux (33)(34)(35), this was shown to be due to reduced Glut-1 expression rather than hexokinase activity.…”
Section: Discussionmentioning
confidence: 99%